2017
DOI: 10.1016/j.jacc.2017.06.054
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship of Alcohol Consumption to All-Cause, Cardiovascular, and Cancer-Related Mortality in U.S. Adults

Abstract: Light and moderate alcohol intake might have a protective effect on all-cause and CVD-specific mortality in U.S. adults. Heavy or binge drinking was associated with increased risk of all-cause and cancer-specific mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
216
5
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(241 citation statements)
references
References 26 publications
13
216
5
7
Order By: Relevance
“…Dr. Braillon cites one study on poor performance of hepatic steatosis index (HSI), but even this study reports HSI to have “performed well in terms of discriminative ability for the overall population,” with an area under the receiver operating characteristic curve of 0.83 for diagnosis of NAFLD Categorization of alcohol use in our study is not arbitrary and is consistent with the established literature As explained in the methods section of the study, alcohol use was defined using the average number of drinks per day over a period of 12 months, and the participants did not have to be daily or “continuous” drinkers.…”
supporting
confidence: 62%
“…Dr. Braillon cites one study on poor performance of hepatic steatosis index (HSI), but even this study reports HSI to have “performed well in terms of discriminative ability for the overall population,” with an area under the receiver operating characteristic curve of 0.83 for diagnosis of NAFLD Categorization of alcohol use in our study is not arbitrary and is consistent with the established literature As explained in the methods section of the study, alcohol use was defined using the average number of drinks per day over a period of 12 months, and the participants did not have to be daily or “continuous” drinkers.…”
supporting
confidence: 62%
“…Studies in the general population have observed lower risks of frailty and death among those who drink alcohol . However, reduced risks of death were not observed among younger individuals who drink alcohol, suggesting that changes in this behavior over time occurring with illness and aging, as well as selection bias, may result in residual confounding in these cohort studies .…”
Section: Discussionmentioning
confidence: 77%
“…In addition, our findings are consistent with previous studies showing a delicate J-shape relationship between alcohol consumption and mortality, where an increase in alcohol intake quickly becomes harmful. (50) Although recommendations regarding health effects of alcohol remain controversial, our results can be useful when counseling the growing population of patients with NAFLD in the United States on the benefits and harms of alcohol.…”
Section: Discussionmentioning
confidence: 91%